Skyrmions in the presence of isospin chemical potential - Ponciano, Juan Adolfo (2008)
We analyze the existence of localized finite energy topological excitations  on top of the perturbative pion vacuum within the Skyrme model at finite  isospin chemical potential and finite pion mass. We show that there is a  critical isospin chemical potential mu^c_I above which such solutions cease  to exist. We find that mu^c_I is closely related to the value of the pion mass.  In particular, for vanishing pion mass we obtain mu^c_I = 0 in contradiction  with some results recently reported in the literature. We also find that  below mu^c_I the skyrmion mass and baryon radius show, at least for the case  of the hedgehog ansatz, only a mild dependence on the isospin chemical potential.